A case study: the role of method for organizing explicit knowledge in Tenaga Nasional Berhad Distribution, Petaling Jaya, Selangor / Norhasliza Zakaria - Zakaria, Norhasliza (2005)
This project is to study the methods in organizing explicit knowledge in Tenaga Nasional Berhad Distribution (TNBD) in Petaling Jaya, Selangor. This study was focusing on companies' management in managing the explicit knowledge in order to enhance the business and better understand in knowledge management area. This study also finds out the method that Tenaga Nasional Berhad Distribution implemented, the authorized personnel that involves in managing the explict knowledge, and the benefit the company obtain by implement that method. The researcher interested to do the research at TNBD because of this company is the largest electricity utility company in Malaysia which is generates two-thirds of the electricity on the Malaysian Peninsula. From the interview session were conducted with Encik Sansubari, Manager of Renewable Energy Program Coordination in Commercial Affair Department, and Encik Muskizea, Head of IT Department in Tenaga Nasional Berhad, TNBD was implemented System Automation of Interruption Duration Index or SAIDI to organize their explicit knowledge. Furthermore, full cooperation firom TNBD's knowledge worker or known as Master-Data at TNBD to manage explicit knowledge properly was make TNBD's businesses enhance to global